Peptide:glycosaminoglycan hybrid hydrogels as an injectable intervention for spinal disc degeneration12. Issue 19 (8th April 2016) - Miles, D. E.; Mitchell, E. A.; Kapur, N.; Beales, P. A.; Wilcox, R. K.
Abstract : Peptide and glycosaminoglycan hybrid gels undergo self-assembly and result in tuneable mechanical properties with suitability for intradiscal treatments. Abstract : Degeneration of the spinal discs is a major cause of back pain. During the degeneration process, there is a loss of glycosaminoglycans (GAGs) from the proteoglycan-rich gel in the disc's nucleus, which adversely alters biomechanical performance. Current surgical treatments for back pain are highly invasive and have low success rates; there is an urgent need for minimally-invasive approaches that restore the physiological mechanics of the spine. Here we present an injectable peptide:GAG hydrogel that rapidly self-assembles in situ and restores the mechanics of denucleated intervertebral discs. It forms a gel with comparable mechanical properties to the native tissue within seconds to minutes depending on the peptide chosen. Unlike other biomaterials that have been proposed for this purpose, these hybrid hydrogels can be injected through a very narrow 25 G gauge needle, minimising damage to the surrounding soft tissue, and they mimic the ability of the natural tissue to draw in water by incorporating GAGs. Furthermore, the GAGs enhance the gelation kinetics and thermodynamic stability of peptide hydrogels, significantly reducing effusion of injected material from the intervertebral disc (GAG leakage of 8 ± 3% after 24 h when peptide present, compared to 39 ± 3% when no peptide present). In an ex vivo model, we demonstrate that the hydrogels can restore the compressive stiffness of denucleated bovine intervertebral discs. Compellingly, this novel biomaterial has the potential to transform the clinical treatment of back pain by resolving current surgical challenges, thus improving patient quality of life.